PENINGKATAN KEMAMPUAN KOGNITIF DI TAMAN KANAK-KANAK TERUNA KASIH BANGSA SANGGAU LEDO - Rotin, Rotin; Ali, Muhamad; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is that the teacher's learning is still monotonous. The ability to spell in children 5-6 years has not developed as expected. The form of this research is basic action using descriptive method. Based on the results of the study in general it can be concluded that: 1) Planning the learning done is categorized as "good". 2) The learning carried out by the teacher is categorized as "good". 3) Improvement of cognitive abilities, among others: children choose ronce media based on similar colors by 80%, children choose ronce media based on size by 75%, children choose ronce media based on color similar to choosing ronce media by displaying a 1-to-1 correspondence with figures of 75%. Researcher's suggestion is that the teacher can plan ronce media that comes from children's environmental objects.Â Keywords: Cognitive Ability